FIRST REPORT ON HUNTING BEHAVIOR OF MIGRATORY ORIENTAL HONEY-BUZZARD (PERNIS PTILORHYNCHUS ORIENTALIS) TOWARDS MIGRATORY GIANT HONEYBEE (APIS DORSATA DORSATA) (HYMENOPTERA: APIDAE) ON JAVA ISLAND, INDONESIA - Sih Kahono; Dewi M. Prawiradilaga; Djunijanti Peggie; Erniwati Erniwati; Eko Sulistyadi (BRIN Publishing (Penerbit BRIN), 2020)
Both Migratory Oriental Honey-buzzard (Pernis ptilorhynchus orientalis) and migratory giant honeybee (Apis dorsata dorsata) can be found in South-east Asia. The Oriental Honey-buzzard is the main predator of the giant honeybee, prey upon its honeycomb, larvae, and honey. Its existence always follows the migration of the giant honeybee. They stay on Java island during the migratory season. The giant honeybee lives in a large colony and has a powerful sting that is useful for defence against its predators. The bee is among the most dangerous animals since its threatening defensive behavior causes severe impact on the eagle and is even frequently fatal for human beings. Data collections on hunting behavior of the Oriental Honey-buzzard were based on irregular observations and interviews between the year 2003 to 2019. We categorized five hunting behaviors during data collections: flying orientation around the bee’s nest, attack on living nest, failure to collect the living nest, preying upon the newly empty nest, and transferring attack of the angry bee to people nearby. The safest hunting for the Oriental Honey-buzzard is to prey upon newly empty nest left by the honeybee. When the nest was still occupied by the bee colonies, the eagle should develop a strategy to avoid and reduce the risk of being attacked. It sometimes transfers the attack to people nearby.